2004
DOI: 10.3201/eid1012.040452
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Identification of Nipah Virus from Pigs

Abstract: Nipah viruses from pigs from a Malaysian 1998 outbreak were isolated and sequenced. At least two different Nipah virus strains, including a previously unreported strain, were identified. The findings highlight the possibility that the Malaysia outbreaks had two origins of Nipah virus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 13 publications
1
72
1
1
Order By: Relevance
“…Subsequent studies have shown that NiV is widespread throughout Asia and may even produce annual epidemics in countries such as Bangladesh (6,10). The viruses involved in the outbreaks incurred mortality rates in humans varying from 40% to 70% and can be distinguished by nucleic acid sequencing (29,30). To analyze the different parameters involved in the disease induced by the henipaviruses, we developed an animal model in hamsters (22).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have shown that NiV is widespread throughout Asia and may even produce annual epidemics in countries such as Bangladesh (6,10). The viruses involved in the outbreaks incurred mortality rates in humans varying from 40% to 70% and can be distinguished by nucleic acid sequencing (29,30). To analyze the different parameters involved in the disease induced by the henipaviruses, we developed an animal model in hamsters (22).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the distinct clinical representation, host-specific differences in lung pathology have been demonstrated histologically in fixed lung tissue samples from NiV-infected pigs and fatal human cases (Chua et al, 2000;Hooper et al, 2001;Maisner et al, 2009;Middleton et al, 2002;Tanimura et al, 2004;Weingartl et al, 2005;Wong et al, 2002). As porcine and human NiV isolates did not differ in their sequence (AbuBakar et al, 2004), species-specific host factors rather than genetic variabilities must be responsible for the differences in NiV replication in the respiratory tract of pigs and humans. On a molecular level, these host factors are not well understood, not least because direct comparative studies on NiV replication in airway epithelia of the two species have not been performed so far.…”
Section: Introductionmentioning
confidence: 99%
“…The virus was isolated in 1999 from the cerebrospinal fluid of a human fatality. Although Pteropus bats are considered to be a reservoir of the virus (7), human infections in Malaysia were considered to be due to transmission of the virus from pigs (1). In the field, the infection in pigs may go unnoticed or cause respiratory disease and, rarely, encephalitis (porcine respiratory and encephalitis syndrome) (26).…”
mentioning
confidence: 99%